A Persian validation of the burnout assessment tool - Simindokht Kalani; Mahla Dashti Esfahani; Payam Khanlari (BMC, 2024)
Abstract Background Burnout is an increasing public health concern. Its prevalence has extended across diverse professions globally, posing significant challenges to individuals, organizations, and society. This phenomenon has undermined employee well-being, productivity, and organizational effectiveness, making it a critical concern in contemporary work environments. The present study aimed to examine the adaptation and assess the validity of the Persian version of the Burnout Assessment Tool (BAT). Methods The adaptation process included the translation and back-translation of the BAT. Data were collected on a sample of 580 teachers using the convenience sampling. The BAT-Persian and Utrecht Work Engagement Scale were administered to collect the data. The reliability, factorial structure of the BAT-C and BAT-S, and the convergent and discriminant validity of BAT-C and work engagement were explored. Results Confirmatory factor analysis supported a four-factor structure for the core dimensions (BAT-C; exhaustion, mental distance, emotional impairment, cognitive impairment), and a two-factor structure for the secondary dimensions (BAT-S; psychological distress, psychosomatic complaints). In the second-order model, the item loadings on the four factors of BAT-C ranged from 0.35 to 0.85, and on two factors of BAT-S ranged from 0.63 to 0.89. The Persian versions of the BAT-C and BAT-S showed good internal consistency (respectively, α = 0.95 and 0.90). Additional evidence supports the convergent and discriminant validity of the BAT-GR. the BAT‐C and its scales were negatively correlated with work engagement and dimensions (i.e., vigor, dedication, and absorption). Moreover, the BAT‐S and its scales negatively correlated with work engagement and dimensions. Conclusions This study provided evidence that the Iranian version of BAT represents a reliable and valid tool for measuring burnout in the work context. A reliable and valid tool for assessing burnout in the Iranian workplace enables early detection of employee distress, allowing for timely intervention and support. This means that identifying the signs and symptoms of burnout in the early stages can prevent more severe consequences such as absenteeism, reduced productivity, or turnover.